Pengaruh Cross Training dan Kontrak Psikologis terhadap Psychological Well-Being dan Kinerja Karyawan - Mirza Norma Fitalia Rahmi; Irwansyah Irwansyah; Diana Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to provide an overview and empirical evidence of the impact of Cross Training and Psychological Contracts on Psychological Welfare and Employee Performance. The population and sample in this study only consisted of contract workers. Bankaltimtara Samarinda branch which has a total of 72 people. The analytical method applied is PLS (Partial Least Squares) analysis, which is a powerful method for conducting analysis because it is not based on many conjectures. The advantages of PLS ​​are that the sample size does not have to be large, the data used does not need to all have a multivariate normal distribution, and PLS can not only be used in fire theory, but can also describe the influence of latent variables. The results of the study show that cross training can have a significant impact on employee performance at Bank Altimtara which is supported by indicators that have high loading factor values. Cross training can have a significant impact on psychological well being at Bankaltimtara which is supported by indicators that have high loading factor values. Psychological Contracts can have a significant effect on employee performance at Bankaltimtara which is supported by indicators that have high category loading factor values. Psychological Contracts can have a significant impact on psychological well-being at Bankaltimtara which is supported by indicators that have high category loading factor values. Psychological Well Being has a significant impact on employee performance at Bankaltimtara which is supported by indicators that have high category loading factor values. Cross Training has a significant impact on employee performance mediated by psychological well being at Bankaltimtara which is supported by indicators that have high loading factor values. Psychological contracts have a significant impact on employee performance which is mediated by psychological well-being at Bankaltimtara which is supported by indicators that have high category loading factor values.